Agricultural Science and Technology Indicators: 2018 Global Food Policy Report Annex Table 1 - Agricultural Science and Technology Indicators (International Food Policy Research Institute, 2018)
Policy makers recognize that increased investment in agricultural research is key to increasing agricultural productivity. Despite this, many low- and middle-income countries struggle with capacity and funding constraints in their agricultural research systems. Agricultural Science and Technology Indicators (ASTI), led by the International Food Policy Research Institute (IFPRI), within the portfolio of the CGIAR Research Program on Policies, Institutions, and Markets works with national, regional, and international partners to collect time series data on the funding, human resource capacity, and outputs of agricultural research in low- and middle-income countries. Based on this information, ASTI produces analysis, capacity-building tools, and outreach products to help facilitate policies for effective and efficient agricultural research.